DIGITAL TRANSFORMATION IN PUBLIC SERVICES: A CASE STUDY OF LAILA 24/7 IN ENHANCING PHARMACEUTICAL AND FOOD SAFETY IN JAKARTA - Rosalina, Ajeng I. (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The rapid advancement of digital technology has revolutionized public service delivery, with innovations like Laila 24/7 emerging as transformative solutions. Implemented by the Jakarta Provincial Drug and Food Control Agency (BBPOM DKI Jakarta), this WhatsApp-based service integrates artificial intelligence (AI) and centralized databases to provide 24/7 access to pharmaceutical and food safety information, complaint handling, and regulatory consultations. This study employs a mixed-method approach—combining case analysis, stakeholder interviews, and performance metrics—to evaluate Laila 24/7's impact. Results demonstrate enhanced accessibility (24/7 responsiveness), efficiency (AI-driven complaint classification), and proactive product safety verification through BBPOM’s integrated database. Challenges include digital literacy gaps among vulnerable groups and cybersecurity risks. The innovation significantly elevates public trust (evidenced by a 97.94% user satisfaction rate) and sets a benchmark for digital governance. Strategic recommendations focus on infrastructure expansion, community-based digital literacy programs, and multi-stakeholder collaboration to ensure inclusive and sustainable implementation.